2017
DOI: 10.1523/jneurosci.2318-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Disruption of Resting-State fMRI, LFP, and Spike Connectivity between Area 3b and S2 following Spinal Cord Injury in Monkeys

Abstract: This study aims to understand how functional connectivity (FC) between areas 3b and S2 alters following input deprivation and the neuronal basis of disrupted FC of resting-state fMRI signals. We combined submillimeter fMRI with microelectrode recordings to localize the deafferented digit regions in areas 3b and S2 by mapping tactile stimulus-evoked fMRI activations before and after cervical dorsal column lesion in each male monkey. An average afferent disruption of 97% significantly reduced fMRI, local field p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 50 publications
1
11
1
Order By: Relevance
“…However, to date, there is no evidence suggesting that anesthesia alters synchronization of resting state signals between layers in two functionally highly related cortical areas. In contrast, our own studies found that rsFC patterns did not change as a function of anesthesia level, indicating that the core intrinsic patterns are preserved under the light anesthesia level we used in our studies (Wu, Yang, & Chen, ). Increases in anesthesia depth only reduced the overall rsFC strength with no noticeable area bias (Wu et al, ).…”
Section: Discussioncontrasting
confidence: 79%
“…However, to date, there is no evidence suggesting that anesthesia alters synchronization of resting state signals between layers in two functionally highly related cortical areas. In contrast, our own studies found that rsFC patterns did not change as a function of anesthesia level, indicating that the core intrinsic patterns are preserved under the light anesthesia level we used in our studies (Wu, Yang, & Chen, ). Increases in anesthesia depth only reduced the overall rsFC strength with no noticeable area bias (Wu et al, ).…”
Section: Discussioncontrasting
confidence: 79%
“…Two main features of the BOLD responses support the conclusion that FUS-induced effects are neural based and circuit specific. First, the overall shape of BOLD signal changes evoked by long FUS blocks is very similar to the typical hemodynamic signal changes evoked by natural tactile stimulation, which are known to be related to increases in spiking activities and local field potentials in areas 3b and 1 of S1, as well as S2, within the monkey somatosensory system 32 , 36 . Second, the FUS-induced responses in these regions differed in magnitude and temporal features between regions.…”
Section: Discussionmentioning
confidence: 68%
“…In the present study, we aimed to address several challenges and questions about the application of FUS neuromodulation of the non-human primate brain using MRI-guided FUS at 7 T. We chose to study the monkey somatosensory system because it has been well characterized using fMRI and intracranial electrophysiology as well as invasive and post-mortem studies 25 , 26 . We have developed robust fMRI paradigms that allow us to reliably map brain touch circuits in non-human primates 27 – 32 . We first established that a FUS transducer could be implemented in a 7 T human scanner, with an optical tracking system to guide transducer placement.…”
Section: Introductionmentioning
confidence: 99%
“…Med-FUS induced BOLD signal changes in areas 3a/3b, MCC, and VPL exhibited a two-phase feature: an apparent signal drop at the beginning of the med-FUS stimulation followed by BOLD signal increases. The overall shape of the BOLD signal changes modulated by long med-FUS blocks is very similar to the typical hemodynamic signal changes evoked by natural tactile stimulation, which are believed to be related to increases in spiking activities and local field potentials in areas 3b and 1 of S1, as well as S2, within the monkey somatosensory system [ 34 , 62 ]. We interpret the responses of the off-target regions as neural-based and activated via inter-regional connections.…”
Section: Discussionmentioning
confidence: 81%
“…Macaque monkeys have been well characterized by fMRI and intracranial electrophysiology as well as by invasive and post-mortem studies [ 27 , 28 ]. We have developed robust fMRI paradigms that allow us to reliably map touch responses in the brains of non-human primates [ 29 34 ], and have demonstrated the ability to detect high-amplitude FUS-induced neuromodulation effects [ 23 ], in which the used FUS was twice as high in amplitude. we refer to the current parameters as “med-FUS” to indicate medium amplitude.…”
Section: Introductionmentioning
confidence: 99%